The role of change in self‐criticism across young adulthood in explaining developmental outcomes and psychological wellbeing. Issue 4 (27th September 2018) - Michaeli, Yossi; Kalfon Hakhmigari, Maor; Dickson, Daniel J.; Scharf, Miri; Shulman, Shmuel
Abstract: Objective: Past research has confirmed the role of self‐criticism in numerous forms of psychopathology and negative interpersonal outcomes. However, the majority of these studies were cross‐sectional and have not addressed the role of possible changes in self‐criticism across time for future outcomes. The current study investigated the degree to which changes in self‐criticism during young adulthood precede better psychological outcomes beyond the contribution of their baseline levels. Method: A total of 168 Israeli emerging adults were followed for 12 years. Participants completed assessments of self‐criticism at age 23, 24, 26.5, and 29, and of developmental tasks and psychological adaptation at age 35. Analyses assessed the extent to which the intercept and linear slope of self‐criticism were associated with assessments of coping with age‐related tasks and psychological well‐being at age 35. Results: Findings indicated that decreases in self‐criticism between the ages of 23 and 29 were associated with better coping with age‐related task outcomes and psychological health at age 35. Conclusions: These findings are among the first to show that decreases in self‐criticism serve as important precursors of coping with age‐related tasks and psychological outcomes and point to the positive contributions of changes in personality attributes for future development.